Implikasi Kebijakan Pengelolaan Pertambangan Batubara Terhadap Eksistensi Masyarakat Hukum Adat Di Samarinda - Yulianingrum, Aullia Vivi; Nurfadillah, Mursidah; Riziq, Sayid Muhammad; Novitadiningrum, Adinda (Fakultas Syariah INSURI Ponorogo, 2023)
Implementation of Undang-Undang Cipta Kerja and Undang-undang Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining is considered by the Government as a form of policy for managing mining business activities which in fact has a significant impact on environmental damage and the existence of indigenous peoples around the coal mining area. This study aims to describe the implications of coal mining management policies for the existence of indigenous peoples in Samarinda. The research method used is legal research with a qualitative non-doctrinal approach, with the research location in Pampang Village, Samarinda. The data collection techniques are in the form of interviews and observations by purposive sampling. The results of the study show that natural resource policies provide too much convenience for investors, thus creating implications for the existence of customary law and management of business licenses that are out of control. In conclusion, the impact of environmental damage is so great that it is necessary to deregulate and de-bureaucratize the granting of mining business permits to prevent the extinction of customary values ​​and the existence of indigenous and tribal peoples.